(untitled) (Journal of Economic Research & Business Administration, 2024)
The article pays special attention to the most currently discussed topic – the development of the world economy in the post-pandemic period. In particular, the possibilities of increasing trade and economic relations between Kazakhstan and Slovenia in this difficult period, the international economy’s recovery from the crisis experienced during the period of COVID - 2019 are being considered. The methodological basis of the study is empirical data that were taken from statistical documents and grouped in tabular and schematic form, a comparative analysis of the trade turnover of the two countries was carried out. Countries around the world have faced many difficulties related to problems in logistics, the functioning of production facilities, ensuring the availability of various tourist destinations, etc. That is why, in modern conditions, the development of cooperation and the preservation of friendly relations between states is the main task. The analysis of the indicators of the foreign trade turnover of Slovenia and Kazakhstan is carried out, indicators for the main exported and imported goods are given, the ways taken by the state to overcome difficulties are considered. The author considers the possibilities for further cooperation between the two countries in order to successfully overcome the difficulties caused by the pandemic and stabilize the economy of Slovenia by strengthening cooperation with Kazakhstan. The value of the conducted research lies in a detailed comparative characteristic of the post-pandemic mutual trade turnover of the two countries and promising development directions for the economy of Kazakhstan are given. Key words: agro-industrial complex, COVID-2019, post-pandemic period in the economy, economy of Slovenia, economy of Kazakhstan.